L'incidenza di psicosi maniaco-depressiva sul grave difetto di discrezione di giudizio - Leszczy?ski, Grzegorz ("Iustitia et iudicium" ; 1, 2010)
The article attempts to indicate manic-depressive psychosis as a possible cause of incapacity to matrimonial consent. The author firstly examines various definitions of the term psychosis and he describes two characteristic episodes of manic-depressive psychosis and their symptoms. Secondly, the influence of depressive episodes on the grave lack of discretion of judgement as defined in c. 1095 2° is being discussed in the context of rotal sentences. Conclusion: grave mania and grave depression are causes for nullity due to the incapacity to give the required matrimonial consent